Serum concentration of homocysteine in spontaneous feline chronic kidney disease. (December 2019) - Giraldi, M.; Paltrinieri, S.; Curcio, C.; Scarpa, P.
Highlights: Serum homocysteine (Hcy) was measured in healthy cats at risk of chronic kidney disease (CKD) and in cats with CKD. The enzymatic method was validated and showed high precision and accuracy in feline serum. Hcy increased in cats with CKD compared with cats at risk and increased with International Renal Interest Society (IRIS) stage. Preliminary results of our longitudinal study suggested that Hcy might be useful to predict disease progression. Abstract: Serum homocysteine (Hcy) increases in people and dogs with chronic kidney disease (CKD). Hyperhomocysteinemia (HHcy) has also been associated with CKD-related hypertension and proteinuria. The aims of this study were to: (1) validate an enzymatic method for quantification of Hcy in feline serum; (2) evaluate whether HHcy was associated with the presence and severity of CKD, proteinuria or hypertension; and (3) determine whether HHcy could predict disease progression. The intra- and inter-assay coefficients of variation (CVs) and the recovery rates of linearity under dilution and spiking recovery tests of the enzymatic method were 3.1–6.7%, 11.6–12.5%, 96.9 ± 5.4% and 96.9 ± 5.4%, respectively. Healthy cats at risk of CKD ( n = 17) and cats with CKD ( n = 19) were sampled over a 6-month period (63 samples in total). Cats with CKD had significantly higher Hcy concentrations ( P = 0.005) than cats at risk. The concentration of Hcy was higher ( P = 0.002) in moderate-severe CKD than in mild CKD and correlated moderately with serum creatinine ( P < 0.0001; r = 0.51). The concentration of Hcy increased with the magnitude of proteinuria and correlated weakly with urinary protein to creatinine ratio ( P = 0.045; r = 0.26). HHcy was not associated with hypertension. At the time of enrollment, Hcy concentration was significantly higher ( P = 0.046) in cats that developed CKD compared to cats that remained stable. The enzymatic method for Hcy measurement in feline serum was precise and accurate. HHcy was relatively common in cats with advanced CKD and seemed to predict disease progression, but further studies are warranted.